Hydrothermal carbonization of biomass from landscape management – Influence of process parameters on soil properties of hydrochars. (15th May 2016) - Röhrdanz, Michael; Rebling, Tammo; Ohlert, Jan; Jasper, Jan; Greve, Thomas; Buchwald, Rainer; von Frieling, Petra; Wark, Michael
Abstract: Besides pyrolysis the technology of hydrothermal carbonization (HTC) is tested to produce hydrochars for soil improvement. The chemical and physical properties of the hydrochars mainly depend on the feedstock and the process parameters reaction time and process temperature. Systematic investigations on the influences of these process parameters on soil properties of hydrochars like water holding capacity (WHC) and cation exchange capacity (CEC) are missing. In this study, a rush-rich biomass was carbonized within defined HTC process conditions under variation of reaction time and process temperature to produce hydrochars. Analysis of WHC, CEC, the elemental composition and Fourier-transform infrared spectroscopy (FT-IR) were performed to evaluate the influence of HTC process conditions on the pedological hydrochar properties. The results indicated that at increasing reaction severity (reaction time and process temperature) WHC and CEC decreased as well as the elemental O/C ratio. The decrease of WHC and CEC is based on the decrease of the hydrochar surface polarity. However, even the lowest WHC and CEC of investigated hydrochars still exceeded those of pure quartz sand by factors of 5–10. An application of hydrochars produced at severe HTC conditions could improve WHC and CEC of sandy soils. This has to be investigated in further studies. Highlights: HTC process conditions influence water holding and cation exchange capacities. Hydrochars WHC and CEC exceed those of quartz sand by factors of 5–10. CEC of hydrochars produced at more severe HTC conditions are comparable to Cambisol. Highest WHC and CEC after HTC at 180 °C and 15 min. Compromise between high WHC and CEC and high biological stability has to be found.